Characterization and quantification of blood cells from the umbilical cord of dogs - Nakage, APM; Santana, A. E.; de Capua, MLB; Godoy, A. V. (Amer Soc Veterinary Clinical Pathology, 2005)
Background: Models for the study of hematopoietic stem cells in dogs provide important information for bone marrow transplantation in humans. Recent studies have reported the importance of human umbilical cord blood (UCB) as an alternative to allogenic bone marrow for hematopoietic reconstitution. However, there are no studies on the UCB cells of dogs. Objective: the aim of this experiment was to characterize and quantify the blood cells of the umbilical cord of dogs. Methods: the blood of the umbilical cord of 20 neonatal dogs, delivered at term, with a median gestation time of 58 days, was collected with a 5-mL syringe containing EDTA. Total RBC, WBC, and platelet counts, HCT, hemoglobin (Hgb) concentration, and RBC indices were determined using an automatic cell counter. The differential leukocyte count was determined manually in blood smears stained with May-Grunwald-Giemsa. Reticulocyte percentages were determined on blood smears stained with brilliant cresyl blue and counterstained with May-Grunwald Giemsa. Results: the MCHC and numbers of RBCs, WBCs, neutrophils, and eosinophils in UCB were lower as compared with reference values for the peripheral blood of healthy neonatal and adult dogs; whereas, the MCV and reticulocyte percentages were higher. Conclusion: Erythrocyte macrocytosis and hypochromasia in UCB were consistent with marked reticulocytosis and indicative of high erythropoietic activity. The results of this study are an important first step in the characterization of UCB from neonatal dogs.
Keywords: blood cells; bone marrow transplant; dog; hematology; stem cell; umbilical cord